Pengaruh Reliability, Responsiveness dan Emphaty Terhadap Customer Loyality Pada Parahyangan Golf Club Bandung - Dini Haryani; Eva Rachmawati; Ae Suaesih (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2020)
This research was conducted at Parahyangan Golf Club Bandung. The purpose of this study was to determine the relationship of Reliability, Responsiveness, and Emphaty on Customer Loyalty both simultaneously and partially. The method used in this research uses associative descriptive method. This study uses 99 as a research sample using multiple linear regression analysis. Testing the hypothesis in this study using the statistical F-test and t-test. The statistical analysis process uses the SPSS for Windows program. Based on the results of the study, the influence of Reliability, Responsiveness, and Emphaty on Customer Loyalty at Parahyangan Golf Club Bandung conducted with the analysis of the coefficient of determination has an influence meaning that Reliability, Responsiveness, and Emphaty have an effect on Customer Loyalty is influenced by other factors not examined by the authors.